Rat‐ and bat‐pollination of Mucuna championii (Fabaceae) in Hong Kong. Issue 1 (8th October 2020) - Kobayashi, Shun; Gale, Stephan W.; Denda, Tetsuo; Izawa, Masako
Abstract: Mucuna (Fabaceae) species possess gullet‐type flowers that open explosively and which are thought to be specifically adapted for bat‐ or bird‐pollination. However, recent studies have shown that non‐flying mammals are also important pollinators of this genus in Asia. Here we report on the pollination system of Mucuna championii (endemic in southeast China) in Hong Kong. As is typical for the genus, explosive opening is essential for fruit set, but flowers are unable to open in the absence of manipulation by an effective pollinator. Camera trap surveys of three individuals revealed both chestnut spiny rats ( Niviventer fulvescens ) and short‐nosed fruit bats ( Cynopterus sphinx ) to be capable of triggering explosive opening. The number of flowers opened by each species did not differ significantly, and both removed most pollen grains from the flowers they visited, but either species visited different individuals. Sucrose‐rich nectar was secreted by flowers throughout the day. Our results reveal that M. championii can be pollinated by both rats and bats, with this representing only the second report of rat‐pollination in tropical Asia. The sympatric M. birdwoodiana often occurs in close proximity to M. championii and has an overlapping flowering season, suggesting that pollinator segregation may have played a role in shaping the evolutionary ecology of these two species. Abstract : We reported on the pollination system of Mucuna championii (Fabaceae) (endemic in southeast China) in Hong Kong. As is typical for the genus, explosive opening is essential for fruit set, but flowers are unable to open in the absence of manipulation by an effective pollinator. Camera trap surveys reveal that flowers of this species were opened by both chestnut spiny rats ( Niviventer fulvescens ) and short‐nosed fruit bats ( Cynopterus sphinx ), and thus can be pollinated by them.